2021
DOI: 10.14421/jga.2021.63-05
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Buku Stimulasi dan Deteksi Tumbuh Kembang Anak Usia Dini Berbasis ICT

Abstract: In the current era of globalization, parents, teachers, and all elements of society who are in the environment around early childhood learn to provide stimulation that is following the development of children. The wider and more open parenting science that can be accessed by parents, teachers and the community requires appropriate guidelines as a reference source to detect and stimulate children's development based on facts in the field. This is the background for researchers to develop and produce a book on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
0
4
0
9
Order By: Relevance
“…Types of early detection of child growth and development that can be carried out by health workers at the community health center, ECCE and network levels, in the form of: Early Detection of Growth Deviations, Early Detection of Developmental Deviations, Early Detection of Mental-Emotional Deviations (SDICGD (SDIDTK), 2016) Stimulation of children's growth and development is an effort by parents or families to invite children to play in an atmosphere full of joy and affection (Rantina & Rahmanela, 2021). It can be concluded that early detection of child growth and development is an effort to identify potential or problems with a child's development from an early age so that appropriate intervention or stimulation can be immediately provided.…”
Section: Early Detection Of Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Types of early detection of child growth and development that can be carried out by health workers at the community health center, ECCE and network levels, in the form of: Early Detection of Growth Deviations, Early Detection of Developmental Deviations, Early Detection of Mental-Emotional Deviations (SDICGD (SDIDTK), 2016) Stimulation of children's growth and development is an effort by parents or families to invite children to play in an atmosphere full of joy and affection (Rantina & Rahmanela, 2021). It can be concluded that early detection of child growth and development is an effort to identify potential or problems with a child's development from an early age so that appropriate intervention or stimulation can be immediately provided.…”
Section: Early Detection Of Growth and Developmentmentioning
confidence: 99%
“…Factors that influence children's growth and development are grouped into two, genetic (Internal) factors include differences in race, ethnicity, nationality, chromosomal abnormalities, and the influence of hormones from parents. Environmental (External) factors are broadly divided into environmental factors that influence the child while he is still in the womb (prenatal factors) and environmental factors that influence the child's growth and development at birth (post-natal) (Rantina & Rahmanela, 2021).…”
Section: Early Childhood 2-3 Yearsmentioning
confidence: 99%
“…Ciri-ciri pertumbuhan dan perkembangan adalah Bertambahnya ukuran fisik, seperti berat badan, tinggi badan, lingkar kepala, lingkar lengan, lingkar dada, (Rantina et al, 2020). Perkembangan dapat terjadi dari daerah kepala menuju ke arah kaudal atau bagian proksimal ke bagian distal .…”
Section: Tinjauan Pustaka Konsep Tumbuh Kembang Balitaunclassified
“…Stimulasi yang jarang dilakukan dapat meyebabkan gangguan tumbuh kembang yang permanen (Ina & Septiani, 2020). Semakin sering melakukan stimulasi pada anak-anak sesuai dengan tahapan usianya akan membentuk perkembangan anak sesuai dengan karakteristiknya (Ramírez-Luzuriaga et al, 2021;Rantina, Hasmalena, & Karmila Nengsih, 2021).…”
Section: Pendahuluanunclassified
“…Keluarga sangat memiliki peranan penting dalam pemberian stimulasi perkembangan motorik kepada anaknya khususnya ibu dalam mencegah keterlambatan perkembangan anak mereka (Ayuba, 2015;Entoh et al, 2020;Labir, Sulisnadewi, & Sumirta, 2016;Rahmawati, 2019;Rukmini, 2019). Proses tumbuh kembang anak sangat dipengaruhi oleh kondisi keluarga latar belakang seperti tingkat pendidikan orang tua, pekerjaan dan pendapatan orang tua, jumlah saudara dan jenis kelamin, latar belakang budaya, adat istiadat, agama dan asupan gizi seimbang (Prado et al, 2017;Ramírez-Luzuriaga et al, 2021;Rantina et al, 2021). Masalah tumbuh kembang pada anak dapat disebabkan juga oleh faktor genetik dan faktor lingkungan karena kebutuhan dasar tumbuh kembang anak yang tidak tercukupi.…”
Section: Hasil Dan Pembahasanunclassified